The Influence of Product Quality and Brand Image on Indihome Customer Satisfaction in Padang City with Trust as a Mediating Variable - M. Raudhitia Ikhsan; Whyosi Septrizola (CV. ITTC INDONESIA, 2023)
The aim of this research is to analyze: (1) The influence of product quality on Indihome customer satisfaction in Padang City (2) The influence of brand image on Indihome customer satisfaction in Padang City (3) The influence of product quality on trust in Indihome in Padang City (4) The influence of brand image on trust Indihome in the city of Padang (5) The influence of trust on customer satisfaction Indihome in the city of Padang (6) ) The influence of product quality on customer satisfaction Indihome in the city of Padang with trust as a mediating variable (7) ) The influence of brand image on customer satisfaction indihome in the city of Padang with trust as a mediating variable , this type of research is quantitative descriptive research, the number of samples in this research is 210 respondents using purposive sampling techniques, the data analysis method uses SEM analysis using the Smart PLS 4 application. The research results are (1) there is a significant influence of product quality on customer satisfaction of Indihome in Padang City (2) there is a significant influence of brand image on customer satisfaction of Indihome in Padang City (3) there is a significant influence of product quality on trust in Indihome in Padang City (4) there is significant influence of brand image on trust in Indihome in Padang City (5) there is a significant influence of trust in customer satisfaction Indihome in Padang City (6) there is a significant influence of product quality on customer satisfaction of Indihome in Padang City with trust as a mediating variable (7) ) there is a significant influence of brand image on indihome customer satisfaction in Padang City with trust as a mediating variable